FABRICATION OF PHOTOTHERAPY TOOLS WITH SENSORS TEMPERATURE AND TIMER BASED MICROCONTROLLER ARDUINO - Henry Prasetyo; Dian Andrianto; Muhammad Zulyadain (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2022)
Phototherapy is a technology used for therapy in infants who suffer from hyperbilirubinemia or jaundice, this disease is due to the accumulation of bilirubin in the blood which is marked by the skin or the whites of the eyes turning yellow, babies who suffer from this disease are usually called yellow babies or icterus. This Phototherapy tool works by giving a blue light to the baby's skin directly for a certain period of time (depending on the level of bilirubin in the baby). The baby will be exposed to blue light which has a wavelength in the range of 450-490 nm for a certain period of time until the level of bilirubin in the baby's body drops to a safe level. With the advancement of technology, we want to add a little innovation by applying the use of a microcontroller to the phototherapy tool, in this case we add the time and temperature sensor DS18B20 as an indicator that will be displayed on the LCD screen so that it can make it easier for the user to turn off the tool and automatically and can notify the temperature of the baby who is getting sick. is doing this blue light therapy. In this case the time can be set according to user needs. From this research, it was concluded that phototherapy tools can be used to treat bilirubin babies. Advantages of this tool that users can monitor the baby's temperature and turn off the device automatically because we added a temperature sensor and timer to the phototherapy tools